Suppression of innate immune signaling molecule, MAVS, reduces radiation-induced bystander effect. (2nd January 2021) - Jia, Rong; Chen, Yaxiong; Jia, Cong; Hu, Burong; Du, Yarong
Abstract: Purpose: Mitochondrial antiviral signaling (MAVS) protein, located in the mitochondrial out-membrane, is necessary for IFN-beta induction and IFN-stimulated gene expression in response to external stress such as viral invasion and ionizing radiation (IR). Although the involvement of radiation induced bystander effect (RIBE) has been investigated for decades for secondary cancer risk related to radiotherapy, the underlying regulatory mechanisms remain largely unclear, especially the roles played by the immune factors such as MAVS. Material and methods: MAVS gene knockout cells using CRISPR/Cas9 technology were used as donor cells or recipient cells to assess the role of MAVS in RIBE by means of co-cultured system. The micronucleus and γH2AX foci in the recipient cells were counted to demonstrate the degree of RIBE. The reactive oxygen species (ROS) level in the recipient was measured using the fluorescent dye 2′7′-dichlorofluorescein. Results: Firstly, we found that MAVS expression level was different in A549, BEAS-2B, U937 and HepG2 cells. Cell co-culture experiments showed that MAVS participate in RIBE. Interestingly, the RIBE response was more significant in recipient cells with higher level of MAVS (i.e. A549) than that in recipient cells showing lower level of MAVS (i.e. BEAS-2B). Further, the bystander response was dramatically suppressed in MAVS-silenced A549 and BEAS-2B recipient cells. MAVS-silenced recipient cells exhibited lower level of ROS induced by IR. Conclusions: Our results indicated that the innate immune signaling molecule MAVS in recipient cells participate in RIBE. ROS is an important factor in RIBE via MAVS pathway and MAVS may be a potential target for the precise radiotherapy and radioprotection.